The Impact of Work Experience on Entrepreneurial Intention Among Vocational Education Students - Fiandra, Yudha; Yulastri, Asmar; Genefri; Hardian Sakti, Rizki (Journal of Technical Education and Training, 2023)
One entrepreneurship-related subject that has produced a lot of research is the investigation of entrepreneurial intention (EI). This study aims to investigate the impact of students’ work experience across the four categories (SN, ES, ATE, and EE). The methodology employed in this study is quantitative, using a structural equation modelling (SEM) approach. The participants were assigned to multidisciplinary workgroups comprising six to eight individuals with backgrounds in management and engineering. There were five-course iterations between the 2021–2022 academic years. There were 250 students registered for this course. This research supports the belief that instruction in entrepreneurship can improve one’s abilities in this area, even if it does not necessarily result in immediate action. This study highlights the importance of entrepreneurial education in increasing entrepreneurial intention among students. Additionally, students’ belief in their abilities to become entrepreneurs, based on factors such as technical skills, social skills, and risk-taking abilities, is not affected by prior work experience. The study recognises that students’ career experience is essential in understanding the significance of entrepreneurial education in fostering entrepreneurial intention.